Consumer-Brand Relationships under the Marketing 3.0 Paradigm: A Literature Review - Gómez-Suárez, Mónica; Martínez-Ruiz, María Pilar; Martínez-Caraballo, Noemí (Frontiers in Psychology, 2017)
Consumer-brand relationships encompass several dimensions, most of which have attracted growing research attention during the last years. Building these relationships is especially important in the marketing 3.0 era, where it is suggested that customers will choose those brands that satisfy their deepest needs. With these ideas in mind, this article provides a review of two key concepts implied in such relationships: brand love and customer engagement. Although both conceptions focus on different stages of consumer-brand relationships, they actually cover different perspectives on the same process. Moreover, they come from diverse conceptual paradigms: whilst brand love comes from the psychology discipline, engagement derives from diverse areas of the marketing field (e.g., the service-dominant logic perspective). However, their further empirical developments have taken place in marketing. Besides, both terms appear to be applied to different empirical perspectives: brand love is usually linked to the Fast Moving Consumer Goods industry and customer engagement to services.